Utilization of Bio Slurry with Input of Buffalo Faeces and Water Hyacinth (Eichornia crassipes) With Various Doses of MOD (Microorganism Decomposer) on Productivity of Indigofera zollingeriana. - Saudarman Sitanggang; Nurzainah Ginting; Yusuf Leonard Henuk; Yunilas .; Hamdan . (Jurnal Peternakan Integratif, 2017)
Abstract. SAUDARMAN SITANGGANG, 2018: Utilization of Bio Slurry with Input ofBuffalo Faeces and Water Hyacinth (Eichornia crassipes) With Various Doses of MOD(Microorganism Decomposer) on Productivity of Indigofera zollingeriana. Guided byNURZAINAH GINTING and YUSUF LEONARD HENUK.The aim of this research was to inventigate the effect of bio gas slurry with the input ofbuffalo feces and water hyacinth (Eichornia crassipes) with various doses of MOD(Microorganism Decomposer) on Indigofera zollingeriana productivity. This research wasconducted in Parbaba Village, Pangururan District, Samosir Regency of North Sumaterafrom April to November 2017. The design used in this research was split plot design with 4replications. Factor I dose of MOD, M1 = 1 liter / 150 liters and M2 = 2 liters /150 liters.Factor II dose of bio-slurry fertilizer with input of buffalo feces and water hyacinthparameters, P0 = 0 (as control), P1 = 20, P2 = 40. Were plant height, stems diameter,fresh weight production, and dry weight troduction.The results showed that dosage of MOD gave significant effect on plant height, stemdiameter, fresh weight production, and dry matter of Indigofera zollingeriana. Theprovision of bio gas slurry with buffalo faeces and water hyacinth with various doses ofMOD has a significant effect on plant height, stem diameter, fresh weight production, anddry matter. The conclusion of this research that increasing the dose of MOD andfertilization dose of Indigofera zollingeriana gave a better result.Keywords: slurry, buffalo faeces, water Hyacinth, productivity, indigofera zollingeriana